Legal Framework and Preventive Measures Against Doping in the 2023 East Java Provincial Sports Week (PORPROV) - Putri Surya Gemilang; Pudji Astuti (Universitas Negeri Surabaya, 2024)
The doping case involving Indonesian athletes and the sanctions imposed by the World Anti-Doping Agency (WADA) due to Indonesia’s failure to submit 300 anti-doping samples highlights persistent irregularities within the national sports sector. These issues reflect broader systemic weaknesses, including at the provincial level. This study aims to examine the preventive measures taken by the East Java Province KONI against doping and to analyze the obstacles in enforcing Article 103 paragraph (1) of Law No. 11 of 2022 concerning Sports, particularly regarding the health component as it relates to anti-doping regulation during the 2023 East Java Provincial Sports Week (Porprov). The research adopts an empirical-qualitative method using purposive sampling, where experts and relevant events are deliberately selected to provide insights not available from general sources. The findings indicate that anti-doping education has not been evenly distributed across districts and cities in East Java. Furthermore, there were no concrete or systematic efforts by East Java KONI to prevent doping during Porprov 2023. Several obstacles were identified in enforcing Article 103 paragraph (1), including legal ambiguity, weak law enforcement, lack of adequate facilities, and insufficient awareness among athletes and stakeholders. The study recommends enhancing anti-doping education, improving coordination between institutions, and strengthening the legal and institutional framework to ensure effective enforcement of anti-doping regulations in future sporting events at the regional level.